FEASIBILITY STUDY OF ORKNEY'S WINDFARM DEVELOPMENT FOR SELF-SUFFICIENT FOR ENERGY IN ELECTRICITY DEMAND AND ROAD TRANSPORT SECTORS - Prattana Kaewpet; Colin Bullen (Zenodo (CERN European Organization for Nuclear Research), 2022)
In Orkney islands, a number of wind energy projects have been established due to its potential for wind energy development especially as cluster developments on hilltop and moorland. This Self-sufficient Orkney Wind Energy (SOWE) project is trying to follow this pattern of development and has designed as a simple linear development of medium-large scale wind turbines which avoids dominating the landscape, while providing diversification required for the energy security, along with strong economic benefits to the local community. The developer completed preliminary designs and landscape assessment, resulting in the detailed design and the development of 27 wind turbine project for the expectation to generated electricity of 549.2 GWh annually.
Keywords: Power Systems and Technologies; Integrated Energy Systems Optimization